Using Hadith Corpus in Learning Arabic as a Second Language - Wan Muhammad Wan Sulong, Rabihah Mohd Ghazali (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Hadith corpus is a rich linguistic and literary resource for Muslims, as well as a religious and legislative resource. The Hadith corpus contains the Prophet's discourse, which holds a special place in Muslims' hearts. It contains the Prophet's (p.b.u.h.) words, actions, sayings, resolve, moral and ethical characteristics. The Hadith corpus is a vast resource and a vast treasure for the Arabic language, which can be useful while learning Arabic as a foreign language (Arabic L2 henceforth). The purpose of this study is to discuss a decent way to use the Hadith corpus in Arabic L2 to meet the demands of non-native speakers. Three significant corpora are used to analyse Hadith texts namely sunnah.com, islamarchive.cc, and islamweb.net. Based on the findings, this research reveals that if the Hadith text offered meets the learners' needs, it could be a valuable tool for Arabic L2. For students to understand the text correctly, it must also be annotated. In this case, Hymes' 'SPEAKING' model, which considers many contextual aspects that are assumed to be involved in speaking, might be utilised as a foundation for annotating the text's social and situational components. These processes will aid Arabic L2 in comprehending the true meaning of words or text-linguistic forms that may differ from their lexical meanings. Examining the context also enables the investigation of the Arabic language's social and cultural values and conventions.